Mobile Experimentation: closing an educational gap for new student generations? - Costa, Ricardo J. (2017)
The M-learning concept is a consequence of mobile technology evolution, i.e. the appearance of devices like Personal Digital Assistants, smart phones and mobile phones with improved features, namely Java support. It is in the same line of E- learning versus Personal Computers and therefore the counterpart of one E- learning subset, named Remote Experimentation, within M-learning, could be designed as Mobile Experimentation. Remote Experimentation is traditionally regarded as the remote access to real-world experiments through a simple web browser running on a PC connected to the Internet, while Mobile Experimentation may be seen as the access to those same (or others) experiments, through mobile devices, used in M-learning contexts. The emergence of two distinct client types (PCs versus mobile devices) creates new requirements for the remote lab infrastructure, namely the ability to tune the experiment interface according to the characteristics (e.g. display size) of the accessing device. This paper proposes a new architecture for the remote lab infrastructure, namely for the software layer to be based in Java and XML, able to accommodate both Remote and Mobile Experimentation scenarios, this last one being especially important for new student generations keen on mobile technology.